Multi‐Mechanism Antibacterial Strategies Enabled by Synergistic Activity of Metal–Organic Framework‐Based Nanosystem for Infected Tissue Regeneration (Small 14/2023). Issue 14 (5th April 2023) - Xie, Wenjia; Chen, Junyu; Cheng, Xinting; Feng, Hao; Zhang, Xin; Zhu, Zhou; Dong, Shanshan; Wan, Qianbing; Pei, Xibo; Wang, Jian
Abstract : Infected Tissue Regeneration In article number 2205941, Xibo Pei, Jian Wang, and co‐workers report a silver nanoparticle (AgNPs) modified metal‐organic‐framework nanosystem (AgNPs@MOFs) with enhanced photodynamic efficiency and chemotherapy ability for infected tissue regeneration. The photodynamic performance under visible light disrupts bacteria translation process. The chemotherapy process causes destructive effect on bacterial cell membrane. AgNPs@MOFs is suggested as a promising nanomedicine in the future.